Cardiac Electrophysiological Effects of Light-Activated Chloride Channels - Kopton, Ramona A.; Baillie, Jonathan S.; Rafferty, Sara A.; Moss, Robin; Zgierski-Johnston, Callum M.; Prykhozhij, Sergey V.; Stoyek, Matthew R.; Smith, Frank M.; Kohl, Peter; Quinn, T. Alexander; Schneider-Warme, Franziska (Frontiers in Physiology, 2018)
During the last decade, optogenetics has emerged as a paradigm-shifting technique to monitor and 18 steer the behavior of specific cell types in excitable tissues, including the heart. Activation of cation-19 conducting channelrhodopsins (ChR) leads to membrane depolarization, allowing one to effectively 20 trigger action potentials (AP) in cardiomyocytes. In contrast, the quest for optogenetic tools for 21 hyperpolarization-induced inhibition of AP generation has remained challenging. The green-light 22 activated ChR from Guillardia theta (GtACR1) mediates Cl–driven photocurrents that have been 23 shown to silence AP generation in different types of neurons. It has been suggested, therefore, to be a 24 suitable tool for inhibition of cardiomyocyte activity. Using single-cell electrophysiological 25 recordings and contraction tracking, as well as intracellular microelectrode recordings and in vivo 26 optical recordings of whole hearts, we find that GtACR1 activation by prolonged illumination arrests 27 cardiac cells in a depolarized state, thus inhibiting re-excitation. In line with this, GtACR1 activation 28 by transient light pulses elicits AP in isolated rabbit cardiomyocytes and in spontaneously beating 29 intact hearts of zebrafish. Our results show that GtACR1 inhibition of AP generation is caused by cell 30 depolarization. While this does not address the need for optogenetic silencing through physiological 31 means (i.e. hyperpolarization), GtACR1 is a potentially attractive tool for activating cardiomyocytes 32 by transient light-induced depolarization.